2018
DOI: 10.1242/jcs.219071
|View full text |Cite
|
Sign up to set email alerts
|

The unusual flagellar-targeting mechanism and functions of the trypanosome ortholog of the ciliary GTPase Arl13b

Abstract: The small GTPase Arl13b is one of the most conserved and ancient ciliary proteins. In human and animals, Arl13b is primarily associated with the ciliary membrane, where it acts as a guanine-nucleotide-exchange factor (GEF) for Arl3 and is implicated in a variety of ciliary and cellular functions. We have identified and characterized Trypanosoma brucei (Tb)Arl13, the sole Arl13b homolog in this evolutionarily divergent, protozoan parasite. TbArl13 has conserved flagellar functions and exhibits catalytic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 97 publications
3
33
0
Order By: Relevance
“…by lacking the proline-rich region or the coiled-coil. Recently, Zhang et al (2018) identified a non-canonical Arl13 gene from Trypanosoma brucei containing the DD_RI_PKA domain (Dimerization/Docking domain of the Regulatory subunit of protein kinase A (PKA)) that is essential for targeting of T. brucei Arl13 to the cilium. Our analysis revealed that the same protein architecture is present also in Euglena gracilis , suggesting it is a synapomorphic character for the whole Euglenozoa phylum (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…by lacking the proline-rich region or the coiled-coil. Recently, Zhang et al (2018) identified a non-canonical Arl13 gene from Trypanosoma brucei containing the DD_RI_PKA domain (Dimerization/Docking domain of the Regulatory subunit of protein kinase A (PKA)) that is essential for targeting of T. brucei Arl13 to the cilium. Our analysis revealed that the same protein architecture is present also in Euglena gracilis , suggesting it is a synapomorphic character for the whole Euglenozoa phylum (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…After digestion, the magnetic beads were removed, and the peptide solution was subjected to LC-MS/MS analyses. Proteomics data were analyzed with MASCOT Server 2.4.0 (Matrix Science) and the T. brucei protein database (TbruceiTREU927, release 28) as previously published (71). The identification threshold was set at a 1% false discovery rate, and the estimation of absolute protein amount-the "protein content"-was calculated based on the exponentially modified protein abundance index (emPAI) (72).…”
Section: Methodsmentioning
confidence: 99%
“…TbArl13 interacts and catalyses nucleotide exchange on both TbArl3A and TbArl3C, but not TbArl3B. Consistently, only TbArl3A and TbArl3C exhibit flagellar biogenesis effects upon overexpression of the GTP-locked mutants (24).…”
Section: Introductionmentioning
confidence: 72%
“…The flagellum of T. brucei has both signalling and motility functions (23) and is crucial for the viability and pathogenesis of this parasite. Both IFT and LIFT pathway components have been identified in T. brucei (22,24). While the function and regulation of the IFT pathway has been extensively characterized (22), the presence of a conserved LIFT pathway in T. brucei was only recently recognized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation